The effectiveness of the use of shark dorsal fin photo-identification methods to aid in the conservation of Carcharodon carcharias and Carcharhinus brachyurus - Maroen, Megan Melissa (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.